Gender and domestic violence: contemporary legal practice and intervention reforms - Russell, Brenda; Hamel, John (Oxford University Press, 2022)
Introduction - the problem with the gender paradigm / John Hamel, Ph.D. & Brenda Russell, Ph.D -- What we currently know about the prevalence, causes and dynamics of intimate partner violence / Elizabeth Bates, Ph.D. & Alexandra Papamichail, Ph.D -- The Law enforcement response to IPV : toward a gender-neutral approach / Brenda Russell, Ph.D & Emily Seisler, BA. BA -- Gender, sex, and the prosecution of intimate partner violence / Jennifer Cox, Ph.D., Elizabeth MacNeil, B.A. & Hannah Lind, B.A -- Challenges and strategies in mounting a legal defense in IPV Criminal Cases / Charles Dresow, Esq -- Intimate partner homicides and the battered person syndrome / John Hamel, Ph.D, Don Dutton, Ph.D., & Alexandra Lysova, Ph.D -- Jury decision making : understanding and overcoming bias in the courtroom / Brenda Russell, Ph.D & Blake McKimmie, Ph.D -- Guidelines for domestic violence and child custody litigation / David Pisarra, Esq -- Custody and intervention recommendations in family law cases : a gender-inclusive framework / John Hamel, Ph.D. & Kelly Baker, Ph.D -- The same coin : intimate partner violence, child abuse, and parental alienation / Jennifer Harman, Ph.D. & Edward Kruk, Ph.D -- Holding perpetrators accountable : evidence-based interview and assessment procedures / John Hamel, Ph.D. & Liam Ennis, Ph.D -- Risk-needs-responsivity (RNR) informed approaches to batterer intervention treatment / Amie Roberts, LMH Counselor, CPM -- Couples and family interventions for intimate partner violence / Victoria Bennet, M.A., Janella Chu, B.S., Deanna Pollard, M.A., & Julia Babcock, Ph.D. -- Restorative justice alternatives / Briana Barocas, Ph.D. & Rei Shimizu, LMSW, Ph.D.